The Impact of Working Memory on Language Gain of Corrective Feedback: A Meta-analysis - Liping, Chen (Politeknik Negeri Padang, 2023)
The theme of working memory has been attracting increasing interest in second language acquisition because working memory is one important cognitive variable affecting the language learning process. Previous research has focused on the relationship between working memory and corrective feedback, but the impact of the methodological factors used to measure working memory and corrective feedback in those studies on the effectiveness of working memory and corrective feedback remain unclear. The current study provides a meta-analysis of studies of working memory on the effects of language gains after corrective feedback. In this meta-analysis, samples from 12 primary studies involving 489 participants were retrieved to calculate average effect sizes of the correlations between working memory and language gains of oral corrective feedback. The results found that working memory has a positive small effect sizes on language gains of oral corrective feedback (r =.321). The findings also showed the methodological factors had an impact on the correlation between working memory and language gains of oral corrective feedback (e.g., types of corrective feedback provided, measures of working memory used, research setting of studies, and academic status of participants). These findings make a better understanding of the working mechanics of CF and WM. These findings also make methodological suggestions for future research on the study of WM on language outcomes of CF in second language acquisition.